The effect of leagile supply chain on supply chain performance: the moderating role of information sharing - Abdulame, Susan Sabah (2020)
Presently, organizations seek continuous improvement in Supply Chain Performance (SCP). While the supply chain performance (SCP) of an organization can be continuously enhanced, the Supply Chain Strategy (SCS) is becoming more complex due to changing customer needs. Based on the existing literature, Leagile Supply Chain (LASC) can be an essential requisite to improve Supply Chain Performance (SCP) by addressing cost, quality, lead time and responsiveness issues, particularly in environments with high uncertainty levels. Hence, the purpose of this study was to provide empirical evidence based on the Contingent Resource-Based View (CRBV) theory and the Strategic Choice Theory (SCT) that support the relationships that exist between LASC and SCP with the moderating effects of Information Sharing (IS). A quantitative research was conducted to investigate the relationship among the variables, through the cross-sectional survey method by using the stratified random sampling procedure to gather responses from 235 large manufacturing industries in Iraq. At the end of the data collection phase, the study managed to obtain 157 usable responses constituting an effective response rate of 67 percent. On applying the Partial Least Squares Structural Equation Modeling (PLS-SEM), the fi di s indicate that LASC has a significant positive relationship with all of the SCP di ns, i.e. Supply Chain Cost (SCC), Supply Chain Quality (SCQ), Supply Chain Le e (SCLT) and Supply Chain Responsiveness (SCR). IS is also positively effec h SCC, SCQ, SCLT and SCR. More importantly, IS significantly and osit oderates the relationship between LASC and the SCP dimensions (i.e. SCC, SCQ and SCR). The results also reveal that the moderating effect of IS in the p between LASC and SCLT dimension is positive but not significant. In y, the impact has increased more on the SCC, SCQ and SCR than it was without the moderating effects. These results provide valuable insights to both practitioners and the academia to further understand the effects of LASC and SCP with the moderating effects of Information Sharing (IS) in the large manufacturing industries in Iraq. Finally, the research limitations are discussed and suggestions on the extended area of research are recommended for future researchers.